VARIASI DIALEK BAHAS A JAWA DI KABUPATEN KEBUMEN (KAJIAN SOSIODIALEKOLOGI) - Ambar Pujiyatno; Soepomo Poedjosoedarmo (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2008)
This research describes the differences of the Javanese of the dialectal varieties in Kebumen  Regency in the field of phonology, morphology, lexicon, and speech level; maps the Javanese dialectal varieties in Kebumen Regency; and describes the geographical and sociocultural factors causing these differences. The data were taken from the seven observation areas through interviewing, recording, and introspection technique. The interview was conducted by asking the questionnaires to the informants. The interview were recorded. In addition, other data were collected through recording the actual utterances in which the items of the questionnaires are spoken. Finally, the introspection technique was also applied to complete the data because the researcher is the native speaker of BJKK.                                    The conclusions of this research are (1) Kebumen Regency is a border or mixing of two Javanese dialects, (2) The regions that have easy access are easier  in getting the influence of bandek Javanese, (3) These regions that are difficult to reach tend to defend the language, (4) The other regions have more varieties. (5) The influence of Bandek Javanese comes  through lexicons, (6) The development between krama ngoko speech level and lexicons is different. The development of krama-ngoko speech level is gained through education and occupation, (7) Some regions have Krama-ngapak Javanese speech level, (8) BJKK has [a] and [o] speech level models, (9) There is a phonological difference between Bandek Javanese an Ngapak Javanese.